Knowledge for Governance - Glückler, Johannes; Herrigel, Gary; Handke, Michael (Knowledge and Space, 2020)
This open access book focuses on theoretical and empirical intersections between governance, knowledge and space from an interdisciplinary perspective. The contributions elucidate how knowledge is a prerequisite as well as a driver of governance efficacy, and conversely, how governance affects the creation and use of knowledge and innovation in geographical context. Scholars from the fields of anthropology, economics, geography, public administration, political science, sociology, and organization studies provide original theoretical discussions along these interdependencies. Moreover, a variety of empirical chapters on governance issues, ranging from regional and national to global scales and covering case studies in Australia, Europe, Latina America, North America and South Africa demonstrate that geography and space are not only important contexts for governance that affect the contingent outcomes of governance blueprints. Governance also creates spaces. It affects the geographical confines as well as the quality of opportunities and constraints that actors enjoy to establish legitimate and sustainable ways of social and environmental co-existence.